Using the spirometry to indicate respiratory exercises for elderly with Parkinson's disease - Daniela Guimarães; Gabriel Duarte; Karen Trippo; Graziella Furtado; Jamary Oliveira Filho; Daniel Dominguez Ferraz (Editora Champagnat, 2018)
Abstract Introduction: Respiratory dysfunction is the main cause of death in Parkinson's disease (PD) patients and bronchoaspiration pneumonia is the most common clinical respiratory complication. Objective: To assess respiratory function of elderly with PD in mild to moderate phase of the disease. Methods: A cross-sectional study was carried. Elderly in 2 to 3 PD Hoehn & Yahr stage have participated. A single researcher has evaluated maximal inspiratory pressure (MIP), maximal expiratory pressure (MEP), thoracoabdominal amplitude, forced vital capacity (FVC) and expiratory volume in the first second (FEV1). Results: Sixty elderly have participated and their all spirometry and manovacuometry parameters presented significant differences (p < 0.05) comparing with predicted values, except for FVC (p = 0.25). Only umbilical level did not reach normal values on cirtometry parameters. Patients classified as a restrictive disorder presented significant decrease in thoracic expandability. However the participants classified as an obstructive disorder showed significant decrease in expiratory muscle strength and peak expiratory flows. Conclusion: Elderly in mild or moderate phase of PD presented reduction in respiratory parameters. Spirometry showed to be an important tool to evaluate respiratory function and to indicate the modality of respiratory exercise. Our results suggest the indication of thoracic flexibility exercises for patient with PD classified as restrictive disorder and strength exercise of respiratory muscles for those classified as obstructive disorder.